Analysis of student perceptions of problem-solving learning and peer assessment - Yustinus Maksimilianus Dhey Nesi; Sentot Kusairi; Arrika Wifqotu Lailin Nafisah (Universitas PGRI Kanjuruhan Malang, 2022)
Problem solving is one of the mandatory skills for students in the 21st century, especially in physics subjects. This study aims to determine the students' ability to solve parabolic motion problems, to determine students' perceptions of learning in solving parabolic motion problems, to investigate the results of peer assessments carried out by students, and to determine students' perceptions of the implementation of peer assessment. This research method uses qualitative research procedures with a phenomenological approach. This research was conducted on 25 high school students in Ende district. The results of data analysis showed that the article met four indicators of problem-solving ability according to Polya, namely understanding the problem, planning a solution, solving the problem according to plan, and re-checking the evaluation results. The problem ability of students in this study was obtained with the results of 53.06 being included in the sufficient category. Future studies should give priority to providing instruction and training before giving peer assessment.